Analysis of immunity to febrile malaria in children that distinguishes immunity from lack of exposure. - Bejon, P; Warimwe, G; Mackintosh, C; Mackinnon, M; Kinyanjui, S; Musyoki, J; Bull, P; Marsh, K (2009)
In studies of immunity to malaria, the absence of febrile malaria is commonly considered evidence of "protection." However, apparent "protection" may be due to a lack of exposure to infective mosquito bites or due to immunity. We studied a cohort that was given curative antimalarials before monitoring began and documented newly acquired asymptomatic parasitemia and febrile malaria episodes during 3 months of surveillance. With increasing age, there was a shift away from febrile malaria to acquiring asymptomatic parasitemia, with no change in the overall incidence of infection. Antibodies to the infected red cell surface were associated with acquiring asymptomatic infection rather than febrile malaria or remaining uninfected. Bed net use was associated with remaining uninfected rather than acquiring asymptomatic infection or febrile malaria. These observations suggest that most uninfected children were unexposed rather than "immune." Had they been immune, we would have expected the proportion of uninfected children to rise with age and that the uninfected children would have been distinguished from children with febrile malaria by the protective antibody response. We show that removing the less exposed children from conventional analyses clarifies the effects of immunity, transmission intensity, bed nets, and age. Observational studies and vaccine trials will have increased power if they differentiate between unexposed and immune children.